From Kitchen To Carnegie Hall: The Story of the Montreal Women's Symphony Orchestra - Rachwal, Maria Noriega (Second Story Press, 2015)
In the 1940s it was unheard of for women to be members of a professional orchestra, let alone play "masculine" instruments like the bass or trombone. Yet despite these formidable challenges, the Montreal Women's Symphony Orchestra (MWSO) became the only all-women orchestra in Canadian history. Formed in 1940, the MWSO became the first orchestra to represent Canada in New York City's Carnegie Hall and one of its members also became the first Canadian black woman to play in a symphony in Carnegie Hall. While the MWSO has paved the way for contemporary female musicians, the stories of these women are largely missing from historical records. From Kitchen to Carnegie Hall illuminates these revolutionary stories, including the life of the incredible Ethel Stark, the co-founder and conductor of the MWSO. Ethel's work opened doors of equal opportunity for marginalized groups and played an important role in breaking gender stereotypes in the Canadian music world.
Keywords: History / Canada / Post-Confederation (1867-); Music / History & Criticism; Music / Individual Composer & Musician